Improving Organizational Structure through Transformative Assessment Strategies: A Case Study of the Excellence Center of Space Technology and Research (ECSTAR) - Charnvit Munikanond; Borwonrat Kanchanarat; Umaporn Akkathai; Settapong Malisuwan (My University, 2023)
In order to remain competitive in both domestic and international markets, organizations must maintain a state-of-the-art operational system. This starts with a strong foundational structure in regards to decision-making processes, employee behavior management, and effective project management. As leaders work to establish the organization's cultural, social, technological, economic, political, and practical systems, along with values, goals, vision, and mission, the adoption of assessment tools is crucial. Although there are various types of assessment tools available, each focusing on different aspects of organizational leadership and development, the ones discussed in this paper aim to drive growth, change, and transformation. The ECSTAR case study highlights that organizations that invest time and resources into mastering strategic management skills and following the frameworks outlined in this paper will undergo a transformative process, leading to enhanced staff collaboration and increased organizational productivity. A strong organizational presence stems from a well-implemented framework at all levels, providing guidance, motivation, and setting standards of excellence and professionalism.
Keywords: Transformative Learning; Excellence; Strategic Planning and Analysis